Karla Reinholda Kupfera spiedogi - Kuzņecova, Kristīne (My University, 2022)
Raksts par Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekciju krājumā esošajiem vācbaltu botāniķa Karla Reinholda Kupfera (1872-1935) personalizētajiem spiedogiemun tintes spiedogu vēsturi.
Karl Reinhold Kupffer stamps
An article about the German-Baltic botanist Karl Reinhold Kupffers (1872-1935) personalized stamps in the Museum of the University of Latvia Botanical and Mycological collections and the history of ink stamps.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Karls Reinholds Kupfers; spiedogi; zīmogi; botānika